Obtención de biodiesel, a escala de laboratorio, a partir de aceites comestibles de desecho: una nueva alternativa de energía renovable (2012)
The biodiesel was obtained from the transesterification of the palm oil used in fritter, in laboratory scale and realized a market research, in restaurants and companies of snacks in Bogotá, D.C., in order to determine the quantity of raw material. Initially the palm oil was characterized, and then it begin with 5.09 g, it was realized transesterification to 70oC and the time of reaction was 3 hours. the efficiency of the process was 77.80 %. Later the biodiesel was analyzed by means of the density 836.6 Kg/m3, acidity index 0.53 mg KOH/g and iodine index 128.82 g I2/100g fat. In agreement to the market research, it would be have approximately 10621,47 tons/ week of eatable oils used in Bogotá.